Pomen obličnostnih zahtev pri oporočnih poslih - Lamovec Hren, Petra (Pravni letopis, 2020)
Every person with a testamentary capacity can make a will and divide his property according to their wishes and preferences. Freedom of disposition is a fundamental policy giving the testator a free choice regarding the form of the will; however, certain formalities that are bound to each form of a will must be followed. Testamentary formalities have different roles, but one common goal - to fulfil testator`s true intentions. There are four main functions of the formalities: evidentiary function, channelling function, ritual or cautionary function and protective function. They enable the court to decide whether a purported will is authentic (evidentiary function). Besides that, they protect testator against imposition or substitution (protective function). Formalities standardise the form and unambiguously show whether the document was meant as a will (channelling function). They also try to impress testator with the seriousness and remind him about the significance of making a will (ritual or cautionary function).
Keywords: dedno pravo; oporoke